ANALISIS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM PERSPEKTIF SHARIAH ENTERPRISE THEORY SEBAGAI WUJUD AKUNTABILITAS PERUSAHAAN (Studi Kasus Koperasi Simpan Pinjam dan Pembiayaan â€œBaitut Tamwil Muhammadiyah Surya Melati Abadiâ€ Jawa Timur) - Utami, Elza Rahmania Dwi (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims to understand the model of corporate social responsibility disclosure at KSPPS â€œBTM Surya Melati Abadiâ€ East Java. In addition, the study is also projected to examine the conformity level of this CSRD with the concepts and characteristics of sharia enterprise theory. The data of this qualitative study are collected through interview involving five informants: chairman of the board, secretary, coordinator of the supervisors, manager, and staff of the accounting manager. Â The Â result Â of Â the Â study indicates Â that Â CSRDÂ  asÂ  a Â whole Â has Â been reported in accordance with the concept of SET, except on the account of zakat maal distribution.Keywords: Corporate social responsibility disclosure, Shariah enterprise theory, Accountability